2017
DOI: 10.1590/1678-98652017000300010
|View full text |Cite
|
Sign up to set email alerts
|

Association between screen time and dietary patterns and overweight/obesity among adolescents

Abstract: Objective The association between screen time and dietary patterns and overweight/obesity among adolescents was analysed in this study. Methods In this cross-sectional study, 963 Brazilian adolescents, aged between 11 and 14 years were evaluated. Body mass index was used to assess overweight/obesity. Dietary patterns and screen time were assessed using qualitative questionnaires. Principal component analysis was used to obtain dietary patterns. Confounder variables were: type of school (public or private), se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
1
18
0
8
Order By: Relevance
“…The components of these patterns are traditional foods eaten in Brazilian meals (“DP I” in lunch and/or dinner; “DP IV” in breakfast and/or snacks between meals). These patterns were also identified in cross-sectional studies conducted with children [ 22 , 24 , 25 ], adolescents [ 21 , 22 , 26 ], and adults [ 55 ] from different regions in Brazil.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The components of these patterns are traditional foods eaten in Brazilian meals (“DP I” in lunch and/or dinner; “DP IV” in breakfast and/or snacks between meals). These patterns were also identified in cross-sectional studies conducted with children [ 22 , 24 , 25 ], adolescents [ 21 , 22 , 26 ], and adults [ 55 ] from different regions in Brazil.…”
Section: Discussionmentioning
confidence: 63%
“…Second, as for all other dietary assessment studies, the self-reported food recall may potentially be subject to misreporting. The PDFQ-3 used in this study proved to be a valid instrument [ 28 ] and has been used to assess dietary patterns and behaviors [ 25 , 26 , 58 ]. The PDFQ-3 was designed to avoid the difficulties associated with children’s assessments of portion size, and to simplify the memory task by prompting only the relevant food items eaten on the previous day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling methods have been described in greater detail elsewhere. 18,19 Based on the prevalence rates of the exposure variables and of each outcome, and considering a study power of 80%, a 95% confidence level, a 10% sample size margin to allow for confounding factors and a design effect of 1.8, this study had sufficient power to: a) detect that prevalence ratios of 0.82 to 0.85 would be protective factors and 1.18 to 1.23 would be risk factors for overweight/obesity; and b) detect that prevalence ratios of 0.50 to 0.60 would be protective factors and 1.68 to 2.01 would be risk factors for abdominal obesity.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…In the current study, one more element was added to the postpartum women's lifestyle, namely the average hours of screen time (e.g., TV, smartphone, tablet, etc.) to measure the respondents' social media use [67][68][69]. For measuring average screen time, we asked three questions.…”
Section: Lifestyle (First Mediator)mentioning
confidence: 99%